High mortality in younger patients with major osteoporotic fractures. Issue 3 (March 2017) - Ray, R.; Clement, N.; Aitken, S.; McQueen, M.; Court-Brown, C.; Ralston, S.
Abstract Summary Data were gathered with regard to mortality after fractures in 1006 younger patients. Results revealed that major osteoporotic fractures of the hip and humerus and drinking alcohol to excess were related to an increased risk of mortality. Introduction Major osteoporotic fractures are known to be associated with increased mortality in older individuals. It is less clear whether this also applies to younger patients. Methods Date were gathered regarding patient demographics, fracture pattern, mechanism of injury, as well as smoking and alcohol intake at the time of injury in consecutive patients aged between 40 and 55 who presented to a UK trauma centre over a 12-month period. Mortality data was taken from the electronic patient records and was cross referenced with data from the General Registrar Office of Scotland. Cox regression analysis was used to identify independent predictors of mortality after adjusting for confounding factors. Results The study cohort consisted of 1006 patients, of which 53% were male. The commonest mechanism of injury was a fall. We obtained complete data regarding mortality for all patients at a median of 5.4 years (inter-quartile range 5.1 to 5.6). During this period, 46 patients were identified as being deceased. The overall standardised mortality ratio for the cohort was substantially increased relative to the age and sex matched general population with a ratio of 3.89 (95% confidence intervals (CI) 1.59 to 6.19). Alcohol excess and fractures involving the humerus and the neck of femur were independent predictors of mortality. Conclusions Young individuals with hip and humerus fractures have a significantly increased mortality risk after their injury relative to the general population. The results of our study suggest that this may be in part due to a high prevalence of alcohol excess.